2013
DOI: 10.1503/cjs.028611
|View full text |Cite
|
Sign up to set email alerts
|

Quality of narrative operative reports in pancreatic surgery

Abstract: Background: Quality in health care can be evaluated using quality indicators (QIs). Elements contained in the surgical operative report are potential sources for QI data, but little is known about the completeness of the narrative operative report (NR). We evaluated the completeness of the NR for patients undergoing a pancreaticoduodenectomy. Methods:We reviewed NRs for patients undergoing a pancreaticoduodenectomy over a 1-year period. We extracted 79 variables related to patient and narrator characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
3
9
1
1
Order By: Relevance
“…About half of the steps in the operative note were described in an adequate manner, which is in accordance with similar published findings in different fields of surgery 1821. According to our results, adding systematic video recording to the traditional operative note would increase the total amount of available adequate information by almost 50 %.…”
Section: Discussionsupporting
confidence: 91%
“…About half of the steps in the operative note were described in an adequate manner, which is in accordance with similar published findings in different fields of surgery 1821. According to our results, adding systematic video recording to the traditional operative note would increase the total amount of available adequate information by almost 50 %.…”
Section: Discussionsupporting
confidence: 91%
“…Their quality audit reinforced these perceptions, as the 40 Roux‐en‐Y gastric bypass NRs they analyzed contained only 62% ± 6.6% of the variables deemed necessary for inclusion. This lack of completeness within NRs was also found in NRs for pancreatic surgery (72.5% completeness for pancreaticoduodenectomy), breast surgery (66% completeness), and upper limb surgery (71.1% completeness) . That fact that our study found a higher average QI inclusion rate (85%) compared to these other studies may reflect the greater emphasis placed on documentation at our institution.…”
Section: Discussionsupporting
confidence: 59%
“…This lack of completeness within NRs was also found in NRs for pancreatic surgery (72.5% completeness for pancreaticoduodenectomy), breast surgery (66% completeness), and upper limb surgery (71.1% completeness). [13][14][15] That fact that our study found a higher average QI inclusion rate (85%) compared to these other studies may reflect the greater emphasis placed on documentation at our institution. Furthermore, junior residents have an informal template that they follow when learning how to dictate reports which could partially account for the fact that junior residents had a higher QI inclusion percentage than senior residents (87% vs 80%) (P .0169).…”
Section: Discussioncontrasting
confidence: 57%
“…Operative reports present a medium to record and potentially measure performance of important quality indicators that affect patients undergoing surgical procedures for cancer [5,6]. However, multiple studies have demonstrated that traditional narrative operative reports (NR) often lack important operative details, which make them inadequate for quality assurance purposes [6][7][8][9][10][11][12][13][14]. More recently, synoptic operative reports (SR), which use pre-defined procedure specific templates, have been developed to standardize operative reporting.…”
Section: Introductionmentioning
confidence: 99%